Preoperative Ultrasonographic Assessment of the Anterior Pelvic Plane for Personalized Total Hip Replacement. (13th October 2017) - Kochman, Andrzej; Goral, Adrian; Kozak, Josef; Marek, Wojciech; Morawska‐Kochman, Monika; Synder, Marek
Abstract : Objectives: Correct positioning of the acetabular component is a key factor in minimizing the risk of dislocation after total hip replacement (THR) surgery. A "safe" orientation of the cup is usually defined by 2 angles measured between its geometric axis and the anterior pelvic plane. However, in the current state‐of‐the‐art approach to THR surgery, the intraoperative orientation of the anterior pelvic plane cannot be measured. Even less is known about the functional orientation of the pelvis, which determines the postoperative orientation of the cup during the patient's everyday activities. The aim of this article is to present an original approach to personalized THR surgery, in which the necessary measurements are done preoperatively without interfering with the surgical work flow, and the individual orientation of the cup is obtained without navigation using standard tools that are available in the operating room. Methods: To quantify the effect of the anatomic conditions on the final orientation of the cup, we measured the orientation of the anterior pelvic plane in 43 patients scheduled for THR using a newly developed noninvasive method based on ultrasonography and mobile devices. Results: Our results confirm a large variability of the pelvic orientation in both supine and standing positions. We further show how this variability affects the final position of the cup and discuss its consequences for the patient. Finally, we explore a few practical solutions for individualized cup placement, including our own approach, which is based on tilting of the operating table. Conclusions: In this work, we show that the common guidelines used today for cup implantation can only be effectively applied to a small portion of the population. In most cases, it is crucial that the orientation of the cup is readjusted for the particular anatomy of the individual patient.